The launch of existence on the Creator and the creature according to Sheikh Al-Ahsa’i - Assistant Lecturer. Sadiq Kazem Maklef (Periodica Journal, 2022)
In this research, we found that the Holy Qur’an is not devoid of mentioning one of the names of God Almighty, or one of His attributes, and that Sheikh Al-Ahsa’i relied on the textual philosophical evidence on this subject
Keywords: evidence; relied; textual; names